Tarry this night - Dunnion, Kristyn, 1969- (Vancouver : Arsenal Pulp Press, 2017)
"A powerful dystopian novel set during a new American civil war, about a polygamist cult leader and his followers. In this eerily relevant, cautionary novel, a civil war is brewing in America. Below ground, a cult led by the deluded and narcissistic Father Ernst is ensconced in an underground bunker, waiting out the conflict. When the "Family" runs out of food, Ruth, coming of age and terrified of serving as Ernst's next wife, must choose between obeying her faith and fighting for survival. Cousin Paul, sent topside to scavenge for food, may return with proof that it is safe for the Family to ascend again. But is it enough to invest all hope in Paul's unlikely return? In this unsettling modern take on the Lilith tale, spirited women resist their violent, racist culture and, in so doing, become outlaws. Family members navigate a secretive and deadly arena where faith eschews autonomy and righteousness precludes mercy. With an unwavering eye, Tarry This Night dares to imagine the unthinkable that is present-day America, offering a place for resistance and hope for a new and better world."--
Issued also in electronic format.